60=6(n-8)

Simple and best practice solution for 60=6(n-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60=6(n-8) equation:


Simplifying
60 = 6(n + -8)

Reorder the terms:
60 = 6(-8 + n)
60 = (-8 * 6 + n * 6)
60 = (-48 + 6n)

Solving
60 = -48 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
60 + -6n = -48 + 6n + -6n

Combine like terms: 6n + -6n = 0
60 + -6n = -48 + 0
60 + -6n = -48

Add '-60' to each side of the equation.
60 + -60 + -6n = -48 + -60

Combine like terms: 60 + -60 = 0
0 + -6n = -48 + -60
-6n = -48 + -60

Combine like terms: -48 + -60 = -108
-6n = -108

Divide each side by '-6'.
n = 18

Simplifying
n = 18

See similar equations:

| -138=-20(v-985)-638 | | 5x+12-14=22 | | y^2(9/2)=-4 | | 3/-95+6=4 | | 1/4(0)+4 | | 6y+=8 | | 2y+12=18 | | -7+2n=4n+7 | | -5/7=r/14 | | x+50-8=-7 | | y/8=25 | | 699=-12(s-980)+75 | | 30x=30x | | 10x-25-3b=4b-1 | | -x^2-4x+3=-6 | | 2(-3/9)=(-3/9)2 | | 10z-5+3z=8-2z | | 6+1x=34 | | 45+15h=120 | | 5(6/7) | | ln(8x-1)=-5 | | 10(2m+10)+8=-6-2(5m-7) | | c=a+x/b | | 9(n+329)+146=146 | | 3(x-8)+6(x-12)=12 | | 3x^2-6=81 | | -3(x+5)=-3(3x+15) | | m/-1.6+7.9=8.4 | | 11b=-198 | | 23/5+12/5y=11 | | 250+12x=20x | | 0.875k=-21 |

Equations solver categories